1969
DOI: 10.1113/jphysiol.1969.sp008680
|View full text |Cite
|
Sign up to set email alerts
|

Muscular, bronchomotor and cardiovascular reflexes elicited by mechanical stimulation of the respiratory tract

Abstract: SUMMARY1. The effects of mechanical stimulation in the nose, epipharynx, laryngopharynx and tracheobronchial tree, and of chemical irritation of the nasal mucosa, were studied on various somatic and autonomic functions in cats.2. Action potentials were recorded from the diaphragm and rectus abdominis muscles of spontaneously breathing cats, and from the phrenic and lumbar nerves of paralysed, artificially ventilated cats. Expulsive processes such as sneezing and coughing evoked from the nasal, laryngopharyngea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
118
1
4

Year Published

1970
1970
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 328 publications
(139 citation statements)
references
References 30 publications
(35 reference statements)
10
118
1
4
Order By: Relevance
“…We defined cough as a burst of EMG activity in the diaphragm (inspiratory muscle) immediately followed by or coincident with burst of activity in the rectus abdominis muscle (expiratory muscle). These criteria are consistent with EMG recordings of respiratory muscle activity during coughing reported by other investigators (Tomori & Widdicombe, 1969;Korpas & Tomori, 1979;Van Lunteren et al, 1989). These criteria also will differentiate coughs from apnoeas or apneusis (no expiratory bursts), augmented breaths (no expiratory bursts), or the expiration reflex (no inspiratory burst).…”
Section: Unanaesthetized Malesupporting
confidence: 85%
See 1 more Smart Citation
“…We defined cough as a burst of EMG activity in the diaphragm (inspiratory muscle) immediately followed by or coincident with burst of activity in the rectus abdominis muscle (expiratory muscle). These criteria are consistent with EMG recordings of respiratory muscle activity during coughing reported by other investigators (Tomori & Widdicombe, 1969;Korpas & Tomori, 1979;Van Lunteren et al, 1989). These criteria also will differentiate coughs from apnoeas or apneusis (no expiratory bursts), augmented breaths (no expiratory bursts), or the expiration reflex (no inspiratory burst).…”
Section: Unanaesthetized Malesupporting
confidence: 85%
“…Cough is produced by coordinated bursts of activity in inspiratory and expiratory muscles (Korpas & Tomori, 1979;Tomori & Widdicombe, 1969). We defined cough as a burst of EMG activity in the diaphragm (inspiratory muscle) immediately followed by or coincident with burst of activity in the rectus abdominis muscle (expiratory muscle).…”
Section: Unanaesthetized Malementioning
confidence: 99%
“…We also discovered that the administration of fentanyl 2 lg.kg )1 before induction attenuates the QTc prolongation associated with laryngoscopy and intubation. Rapid injection of catecholamine, brief stimulation of the sympathetic nervous system, and an imbalance of the cardiac sympathetic tone cause prolongation of the QTc interval [15][16][17][18], which may be related to sympathetic stimulation. However, Korpinen et al [10] reported that b-blockers did not attenuate the QTc prolongation during induction of anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Though tracheal extubation seems to be a benign procedure, multiple studies have shown that it can cause significant increase in BP and HR which may persist till the recovery period. [1][2][3][4][5][6] High degree of sympathetic stimulation, as evidenced by tachycardia, hypertension and increased levels of circulating catecholamines during extubation may prove to be detrimental to their health or to the successful outcome of surgery.Hypertensive subjects exhibit an exaggerated response to laryngoscopy and intubation as well as to awakening and extubation compared to normotensive patients. 7,13,45 Increase in BP, HR and RPP which is a multiple of SBP and HR increases the cardiac workload and the oxygen demand of the myocardium; increasing the risk of developing a fresh episode of myocardial ischemia and infarction in known patients of ischemic heart disease due to a fixed coronary blood flow, along with fall in cardiac index and ejection fraction.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative extubation of trachea is an important event in the course of general anaesthesia which causes a modest (10% to 30%) and transient (lasting approximately 5 to 15 minutes) increase in the HR and BP. [1][2][3][4][5][6][7] Normally these responses are transient in nature hence well tolerated by normotensive healthy subjects.…”
Section: Introductionmentioning
confidence: 99%